2012
DOI: 10.1111/j.1464-410x.2011.10847.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservative and radiological management of simple renal cysts: a comprehensive review

Abstract: What's known on the subject? and What does the study add? Simple renal cysts are a common entity, which may need observation and follow‐up or treatment. The study, for the first time, systematically reviews the indications for follow‐up or radiological treatment of simple renal cysts. To review the conservative and radiological management of simple renal cysts a systematic literature review was performed. Simple renal cysts are commonly found in the adult population. Increasing age is highly associated with it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 90 publications
(325 reference statements)
2
88
0
3
Order By: Relevance
“…These studies indicated that neither the actual size nor size changes were specific to the development of a renal neoplasm. The rate of increase in cyst size in patients with renal cancer was similar to that in other patients of the same age [2] . In our review of simple renal cysts, only 5 cysts were excluded as 2 were Bosniak class III renal cysts (1.1%) and 3 were excised because renal tumor was incidentally detected at another site (1.7%).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…These studies indicated that neither the actual size nor size changes were specific to the development of a renal neoplasm. The rate of increase in cyst size in patients with renal cancer was similar to that in other patients of the same age [2] . In our review of simple renal cysts, only 5 cysts were excluded as 2 were Bosniak class III renal cysts (1.1%) and 3 were excised because renal tumor was incidentally detected at another site (1.7%).…”
Section: Resultssupporting
confidence: 55%
“…Autopsy studies have reported a 50% incidence of renal cysts after the age of 50 years [2] . The prevalence of renal cysts is approximately 10%, ranging from 4% in the third decade to 19% in the sixth decade [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Recently, percutaneous aspiration of renal cysts along with injection of sclerosing agents (such as alcohol) have been explored as a potential treatment option. 10 This approach of percutaneous management can be effective, especially if the cyst is relatively small and para-pelvic in location; however, if more than 200 mL of the original volume persists after this procedure, then surgery becomes necessary. Retroperitoneal approach for open or laparoscopic surgical decortications is well-established.…”
Section: Discussionmentioning
confidence: 99%
“…Bu nedenle kist boşal-tımı, kist içine sklerozan madde enjeksiyonu (en sık etanol kullanılır) ile birlikte yapılmalıdır. 65 Evre III ve IV lezyonlarda cerrahi eksizyon önerilir. Çünkü bu lezyonlarda malignansi riski sı-rasıyla %59-81,8 ve %100'dür.…”
Section: Basi̇t Ki̇stlerunclassified